2013
DOI: 10.2147/ndt.s41074
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral therapy for body dysmorphic disorder: a review of its efficacy

Abstract: The aim of this study was to review the efficacy of different methods of cognitive and/or behavioral therapies used to treat body dysmorphic disorder. We evaluated all case series, open studies, controlled trials, and meta-analyses of cognitive and/or behavioral treatment approaches to body dysmorphic disorder published up to July 2012, identified through a search in the PubMed/Medline, PsycINFO, ISI Web of Knowledge, and Scopus databases. Our findings indicate that individual and group cognitive behavioral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…[ 16 ] There are studies that report of a positive response to psychotherapies such as cognitive behavior therapy. [ 17 18 19 ] Some studies recommend the combination of medications and psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] There are studies that report of a positive response to psychotherapies such as cognitive behavior therapy. [ 17 18 19 ] Some studies recommend the combination of medications and psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative empiricism is imperative for CBT effectiveness. CBT techniques that can aid in BDD treatment and maintenance are cognitive restructuring, self-monitoring, exposure and ritual prevention (E/RP), perceptual retraining, and relapse prevention [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…BDD symptoms may become severe requiring psychiatric hospitalization. Criteria for psychiatric inpatient admission may be met when an individual with BDD is not able to keep up with daily responsibilities or poses immediate risk or danger to themselves [ 7 , 13 , 14 ]. Brief psychological interventions and lengths of stay restrict treatment of BDD in an acute care, inpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…CBT can be conducted by individual session or group therapy session. Findings from the other researcher indicated that individual and group cognitive behavioral therapies are superior to waiting list for the treatment of BDD [61].…”
Section: Cognitive Behavioral Therapy Intervention Of Body Dysmorphicmentioning
confidence: 99%